Ekstrak Biji Klabet Menurunkan Jumlah Sel Spermatozoa pada Kelinci - Sri Wiryawan, I Gusti Nyoman; Ika Wahyuniari, Ida Ayu (Jurnal Veteriner; Vol 10 No 2 (2009), 2009)
Fenugreek seed (Trigonella foenum-graecum) contains saponin diosgenin, wich has an antifertility effect on spermatozoa so it can be used as an oral contraceptive drug. This study was aimedto investigate the effect of fenugreek seed extract to spermatogenic process of rabbit, especially onviability spermatozoa. “Completely randomized control group post-test only design” was used inthis study. The animals were divided into four groups; one control group and three treatmentgroups with six replicates (P0 = control group; P1 = group were given 10 % fenugreek seed extract,1 cc/day; P2 = group were given 20 % fenugreek seed extract, 1 cc/day; P3 = group were given 30 %fenugreek seed extract, 1 cc/day). The extract was given orally once a day in 50 days. After treatment,testicles were sectioned and stained with Hematoxylin Eosin; for qualitative and quantitativemicroscopic analysis. The result of this study showed that the number of spermatozoa were decreasedsignificantly (p<0,05) after receiving 10% fenugreek seed extract 1 cc per day. In conclusion,fenugreek seed extract could reduce the number of spermatozoa.
Keywords: spermatozoa, fenugreek seed extract, rabbit